2020
DOI: 10.3390/cells9051106
|View full text |Cite
|
Sign up to set email alerts
|

L-Selectin/CD62L Is a Key Driver of Non-Alcoholic Steatohepatitis in Mice and Men

Abstract: CD62L (L-Selectin) dependent lymphocyte infiltration is known to induce inflammatory bowel disease (IBD), while its function in the liver, especially in non-alcoholic steatohepatitis (NASH), remains unclear. We here investigated the functional role of CD62L in NASH in humans as well as in two mouse models of steatohepatitis. Hepatic expression of a soluble form of CD62L (sCD62L) was measured in patients with steatosis and NASH. Furthermore, CD62L−/− mice were fed with a methionine and choline deficient (MCD) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 71 publications
1
25
0
2
Order By: Relevance
“…Drescher et al in their study established that CD62L was detected at a higher level in patients with NASH compared to control subjects. The CD62L messenger ribonucleic acid (mRNA) was expressed at a higher level in patients with NASH when compared to patients with simple steatosis [ 19 ]. Flow cytometry also showed a significant increase in the CD62L levels in the intrahepatic immune cells in patients with NASH when compared to control subjects.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Drescher et al in their study established that CD62L was detected at a higher level in patients with NASH compared to control subjects. The CD62L messenger ribonucleic acid (mRNA) was expressed at a higher level in patients with NASH when compared to patients with simple steatosis [ 19 ]. Flow cytometry also showed a significant increase in the CD62L levels in the intrahepatic immune cells in patients with NASH when compared to control subjects.…”
Section: Reviewmentioning
confidence: 99%
“…Flow cytometry also showed a significant increase in the CD62L levels in the intrahepatic immune cells in patients with NASH when compared to control subjects. On performing an experimental study on mice, Drescher et al found that CD62L deficient mice had less pronounced metabolic syndrome, lower fat content both visceral and subcutaneous, and developed a lower grade of NAFLD with lesser ballooning degeneration and lower serum transaminases compared to wild type mice [ 19 ]. His study also demonstrated that there is a reduction in the level of inflammatory cell infiltration in CD62L deficient mice when compared to wild-type mice (WT mice).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations